Monitoring Serum Lipid Profile and Liver Transaminase Levels During Isotretinoin Therapy - Gülseren, Duygu; Bostan, Ecem; Akdoğan, Neslihan; Yalıcı-Armağan, Başak; Doğan, Sibel; Ersoy-Evans, Sibel; Elçin, Gonca; Karaduman, Ayşen (Acta Medica, 2022)
Objective: Isotretinoin is generally chosen as the first line treatment of nodulocystic acne. Close laboratory monitoring is a general practice for many dermatologists to be on the safe side due to the laboratory side effects of isotretinoin. We aimed to determine the laboratory side effects of oral isotretinoin and optimal frequency interval for laboratory monitoring during isotretinoin treatment. Materials and Methods: One hundred patients who were under oral isotretinoin therapy were included in the study; serum lipid levels along with liver transaminase levels were recorded at the baseline, 1-, 3- and 6- months of the therapy. Results: We found that there might be slight elevations in serum aspartate transaminase and lipid levels during isotretinoin therapy (p<0.05, for all). However, statistically significant elevations were observed within the first month of isotretinoin therapy. Conclusions: Frequent laboratory monitoring might not be necessary for all acne patients undergoing isotretinoin therapy. Patients should be screened at the first month of the therapy and then, the intervals can be extended.